Towards Ibn al-Sarraj (d. 316 AH) according to Ibn Malik (d. 672 AH) Investigative study and evaluation (Journal of the College of Basic Education, 2022)
Ibn al-Sarraj left us a huge heritage in the sciences of Arabic, and this heritage has a great status among grammarians, as they frequently quoted from him due to the breadth of his material and the fame of his author, Abu Bakr Ibn al-Sarraj. Ibn al-Sarraj collected the chapters on grammar and morphology and took Sibawayh’s issues and arranged them.